Medicine and charity before the welfare state - Barry, Jonathan, 1956-; Jones, Colin, 1947- (Studies in the social history of medicine., 1991)
This volume offers a broad perspective on the relationship between charity and medicine in Western Europe up to the advent of welfare states in the twentieth century.